Shrimp Cracker Wastewater Treatment with Aerobic Microorganism and Aeration Method (Nusantara Science and Technology Proceedings)
In this study, the effect of aeration time and the ratio of activated sludge and wastewater volume on the decrease in BOD (Biological Oxygen Demand) and levels of COD (Chemical Oxygen Demand) has been successfully investigated. The activated sludge and wastewater were collected from the shrimp cracker industry. This shrimp cracker liquid waste was processed by aerobic method, which started with the wastewater treatment process (with an activated sludge acclimatization process) and closed with an aeration process. The best result was achieved by the ratio of the volume of activated sludge to wastewater 1:2, where an aeration time of 4 hours COD levels can decrease by 82.9% with the final result of 471 mg/l. Moreover, at 10 hours of aeration, the BOD level decreased by 48.9%, with the final result of 442 mg/l. It shows that aerobic biological processes can reduce the levels of BOD and COD present in the liquid waste of shrimp crackers.